Management of peripheral neuropathy symptoms with a fixed dose combination of high-dose vitamin B1, B6 and B12: A 12-week prospective non-interventional study in Indonesia - Hakim, Manfaluthy; Kurniani, Nani; Pinzon, Rizaldy Taslim; Tugasworo, Dodik; Basuki, Mudjiani; Haddani, Hasmawi; Pambudi, Pagan; Fithrie, Aida; Wuysang, Audry Devisanty (Asian Journal of Medical Sciences, 2018)
Background: Peripheral neuropathy is a common condition which can have a significant impact on quality of life. It occurs as a component of several common and rare diseases or can be idiopathic and can present with various symptoms. Aims and Objectives: This study is aimed at evaluating the effectiveness and safety of the fixed dose combination of vitamin B1, B6 and B12in mild to moderate peripheral neuropathy of various etiologies in the Indonesian population. Materials and Methods: This was a prospective, open label, multi-center, single arm observational study (Indonesian Clinical Trial Registry No: INA-KPA0DYA). A total of 411 subjects with mild to moderate peripheral neuropathy of various etiologies, who met the eligibility criteria, were included in the study. A subject was considered to have “completed” the study if the study procedures, up to Visit 3 (one month of treatment) were accomplished. Procedural results and 12-week clinical outcomes are reported. Results: Treatment with combination of vitamin B1, B6 and B12 in subjects with symptoms of PN showed significant improvement in overall Total Symptom Score (TSS), within 14 days. The treatment also successfully reduced individual components of TSS from baseline to Visit 5. A significant percentage reduction was also observed for all the Visual Analogue Scale (VAS) parameters at the end of 12 weeks, while the Quality of Life (QoL) scores increased from baseline to the end of treatment. Conclusions: The fixed dose combination of vitamin B1, B6 and B12 was effective and welltolerated in subjects with mild to moderate peripheral neuropathy, of various etiologies. Asian Journal of Medical Sciences Vol.9(1) 2018 32-40